Population dynamic of the safflower fly, Acanthiophilus helianthi Rossi (diptera: tephritidae) in Gachsaran Region, Iran - Saeidi, Karim; Adam, Nur Azura; Omar, Dzolkhifli; Abood, Faizah (OMICS International, 2013)
Safflower fly, Acanthiophilus helianthi Rossiis one of the most important pests of safflower in most parts of the country. Losses caused by larval feeding lead to disrupted plant activities, reduction in flower buds and ultimately decreased quality and quantity of the crop. In order to study seasonal flight activity of Acanthiophilus helianthi, experiments were conducted for two consecutive years at two different fields in Gachsaran region in 2007-2008. The seasonal flight of Acanthiophilus helianthi was investigated by using Baits traps and collecting samples from eggs, larva and pupa stages of the pest. The results showed that Acanthiophilus helianthi has three generations with an incomplete 4th in the region. Damage of first and fourth generation was very low. The flower heads were mainly damaged by the second and third generation of Acanthiophilus helianthi that happened about ten days after the adult emergency.